Romanticism in Ilya Abu Madi’s Qatrat-al-Tall and Raghunath Choudhary’s Hepah: A Comparative Study - Wahidul Islam; Abul Kalam Choudhury (MAQOLAT: Journal of Islamic Studies, 2025)
Romantic poetry offers a distinctive way to explore love, longing, and emotional depth. The both poems of Ilya Abu Madi’s "Qatrat-al-Tall" (The Dewdrop) and Raghunath Choudhary’s "Hepah" (Desire) are romantic poems that shed lights on these kinds of themes through distinct perspectives. Abu Madi’s poem depicts love as a philosophical mystery, demanding investigation beyond appearances and highlighting romance as a fleeting but meaningful experience, while Choudhary’s poem celebrates sensory devotion, where love is deeply connected with nature and impacts the reader in passionate nostalgia, trying to discover the presence of love in the breeze, sunlight, and ocean. This study analyses how both poets expressed love using symbolism and poetic imagery including their brief biography. One is via thoughtful introspection while the other is through sensory engagement. Though they have cultural differences, but they share the same message like love has an emotional resonance which is universal, divine, and transformative.